Business finance - Isimoya, D.C. (Lagos : Management Science Publishing Limited, 1988)
This edition retains all the features of the first edition. In addition, it is more exhaustively with the issues in capital budgeting. This is guaranteed with the inclusion of the topics.
Including bibliographical references and index.
osa 22/01/2019, rpm 25/01/2019
Loans
Keywords: Finance; Nigeria